Investigating the relationship between gastric polyp and dyspepsia in Iranian patients - Abdi, Saeed; Moradi, Elham; Mohsenifar, Zhaleh (Student Research in Translational Medicine, 2020)
Abstract Background and aim: Chronic dyspepsia is one of the common medical problems in patients referred to internal and gastrointestinal clinics. According to the results of some studies, most patients with dyspepsia are simultaneously suffering from gastric polyps. We aimed to clarify the association of gastric polyp and dyspepsia in an Iranian population. Materials and methods: We enrolled 2772 dyspeptic and 1294 non-dyspeptic subjects in this cross-sectional study, who referred to the gastrointestinal clinic at Ayatollah Taleghani Hospital in Tehran from2016 to 2018.All subjects underwent upper gastrointestinal (GI) endoscopy andpatients with GI malignancy, severe GI bleeding and history of GI surgery excluded from study. They were evaluated for age, sex, endoscopicfindings, gastric polyp (GP) count, size and localization, diagnosticmethods used for histology, and polyp features. The relationshipbetween gastric polyp and dyspepsia was alsoevaluated. Results: In 4066 consecutive upper GI endoscopy in patients with and without dyspepsia, 129 patients (3.2%) had gastric polyps (GPs).The prevalence of GPs was 3.04% and 3.32% in with and without dyspepsia subjects, respectively. There was no observed statistically significant relationship between GPs and dyspepsia (P=0.709). Hyperplastic polyps(HPs)were the most common pathologic form in patients with and without dyspepsia in 53.5% and 34.9% of patients, respectively. The most common location was the gastric antrum polyps (76.7%) and the common size of the polyps was between 5-10 mm in (80.6%) patients. Conclusion: In the present study, there was no statistically significant difference within the pathologic findings of gastric polyp in terms of dyspepsia.Hyperplastic polyps(HPs) are the most common type of pathologic stomach polyps and it is maybe high due to the highfrequency of Helicobacter pylori(H. pylori) infection in our country.